2016
DOI: 10.1016/j.cocis.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Free energy approach to micellization and aggregation: Equilibrium, metastability, and kinetics

Abstract: We review a recently developed micellization theory, which is based on a free-energy approach and offers several advantages over the conventional one, based on mass action and rate equations. As all the results are derived from a single free-energy expression, one can adapt the theory to different scenarios by merely modifying the initial expression. We present results concerning various features of micellization out of equilibrium, such as the existence of metastable aggregates (premicelles), micellar nucleat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Furthermore, the case is even more complex than that, since we have shown that complexation excess free energy is in competition with various quenching energy terms, such as the formation of curved extractant film, different headgroup repulsion, branching of the extractant chains, diluent penetration power, shrinkage of the accessible volume of the ions and water molecules confined in the polar core, energy penalties due to the breaking of stable HDEHP dimers, and dissociation of HDEHP. Only by considering all energy terms that contribute to the formation of the particular aggregate and all the independent system variables can the free energy of the system be properly minimized …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the case is even more complex than that, since we have shown that complexation excess free energy is in competition with various quenching energy terms, such as the formation of curved extractant film, different headgroup repulsion, branching of the extractant chains, diluent penetration power, shrinkage of the accessible volume of the ions and water molecules confined in the polar core, energy penalties due to the breaking of stable HDEHP dimers, and dissociation of HDEHP. Only by considering all energy terms that contribute to the formation of the particular aggregate and all the independent system variables can the free energy of the system be properly minimized …”
Section: Resultsmentioning
confidence: 99%
“…In this latter system and many others like it, there is an emerging consensus that solute aggregation can have a profound impact on the chemical behavior of the organic solution, notably on both the efficiency and selectivity of the process. In fact, reverse micellar solvents with the macroscopic appearance of a homogeneous solution are routinely employed in organic- and biological-based separation, purification, and conversion processes with little understanding of the morphology and arrangement of the micelle domains. , These contemporary applications are revolutionizing fundamental separations concepts by shifting the focus away from the classical enthalpic drivers associated with local, molecular-scale interactions into multiscale-ordering, which is hypothesized to include large entropic contributions that may dominate the energy landscape of bulk behaviors that are hallmarks of coacervation and microemulsions . However, the relationships between the microscopic solute structures and phase behaviors remains largely unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…A general method for the determination of the cmc from linear and nonlinear properties should be based on a common definition of the cmc directly related to the surfactant concentration itself and then derive the experimental properties from this concentration. The concentration model we propose is not the only possible and can still be refined and adapted, but it has so far proven to reproduce excellently several properties, to yield coherent cmc values and to contribute to a better understanding of how properties depend on the surfactant concentrations, the cmc and the transition width [ 23 , 24 , 64 ].…”
Section: Influence Of Nonlinear Property-concentration Relationships On the Cmc Valuementioning
confidence: 99%
“…The big variety of empiric procedures for the determination of the cmc from experimental data is probably also due to the complex physicochemical models and numeric simulations of the micellization process [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Although increasingly sophisticated and precise, these models and simulations are not aimed towards the analysis of experimental data and therefore do not offer fitting functions with the cmc as an adjustable parameter that could be fitted to experimental data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation